ANALISIS EARNING PER SHARE (EPS) DAN ECONOMIC VALUE ADDED (EVA) TERHADAP RETURN SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Siti Mudawanah; Desi Nuraini (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2020)
The purpose of this study was to determine the effect of Earning Per Share (EPS) and Economic Value Added (EVA) on Stock Returns on food and beverage companies listed on the Indonesia Stock Exchange (BEI).The methodology used in this study is quantitative because the research data in the form of numbers and analysis using statistics. And the method of data collection in this research is done through secondary data collection and literature study. In this study, researchers used food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 period as research objects. And the population and sample of this research are 11 companies listed on the Indonesia Stock Exchange (BEI).The hypothesis of this study is to describe whether or not there is an influence between Earning Per Share (EPS) and Economic Value Added (EVA) on stock returns either partially or simultaneously. And the results concluded that partial Earning Per Share (EPS) and Economic Value Added (EVA) had no effect on stock returns, and simultaneously Earning Per Share (EPS) and Economic Value Added (EVA) had no effect on stock returns on food and beverage companies period 2014-2018